Remote sea-surface temperature variations (2001–2019) in Kuwait Bay: Time series analysis in frequency and time domains: DOI: 10.48129/kjs.12873 - Saleh, Ali K.; Al-Anzi, Bader S. (Kuwait Journal of Science, 2022)
There is a recognized need for analyzing the temporal changes of sea surface temperature in various water bodies, and especially the semi-enclosed ones, because of the direct link between sea temperature and aquatic biodiversity. There has been substantial research undertaken on the role of time series analysis as a powerful technique for studying the characteristics of long-term SST changes at regular time intervals. The present paper aimed to study the monthly-averaged MODIS SST data (2001–2019) over Kuwait Bay, i.e., the northwestern corner of the Arabian Gulf. Because different approaches can yield different results, the analysis of the SST time series was conducted using time and frequency domains. The preliminary analysis of the time series reported a significant SST peak in August 2010 that reached nearly 34.2°C (SD = 0.17°C) as a result of the moderate intensity El Niño event in 2010. However, in the preceding year, we observed a cool SST anomaly in the range of –0.5°C to –2.4°C. From the SMK trend test, we found that monthly climatological SST in September exhibited a significant upward trend (S9 = 103,